PENGARUH PENGETAHUAN DAN SIKAP TERHADAP KEAKTIFAN KADER POSYANDU - Reni Permata; Yogik Setia Anggreini (Nursing Arts, 2023)
Posyandu exists today because it has been proven to be a form of community-based health effort, managed and organized for the community, in order to provide convenience to the community in obtaining good basic health services in accelerating the reduction of maternal and infant mortality. The purpose of this study was to influence knowledge and attitudes towards the activity of posyandu kader in the working area of the Puskesmas Sorong Timur. This research is a quantitative research with a cross sectional approach. This study involved 49 respondents. Sampling using total sampling technique. The test used is Chi-square with a confidence level (α) 0.05. Statistical test results obtained that there was an influence between knowledge on the activity of posyandu cadres obtained p-value = 0.000, < α = 0.05. and there is an influence between the attitude and the activity of posyandu cadres, the p-value = 0.000, < α = 0.05. In conclusion, there is an influence of knowledge and attitudes on the activity of Kader posyandu.